Suppression of the HBP Function Increases Pancreatic Cancer Cell Sensitivity to a Pan-RAS Inhibitor - Francesca Ricciardiello; Laura Bergamaschi; Humberto De Vitto; Yang Gang; Taiping Zhang; Roberta Palorini; Ferdinando Chiaradonna (Cells, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is a leading cause of cancer-related death and the search for a resolutive therapy is still a challenge. Since KRAS is commonly mutated in PDAC and is one of the main drivers of PDAC progression, its inhibition should be a key strategy for treatment, especially considering the recent development of specific KRAS inhibitors. Nevertheless, the effects of KRAS inhibition can be increased through the co-inhibition of other nodes important for cancer development. One of them could be the hexosamine biosynthetic pathway (HBP), whose enhancement is considered fundamental for PDAC. Here, we demonstrate that PDAC cells expressing oncogenic KRAS, owing to an increase in the HBP flux, become strongly reliant on HBP for both proliferation and survival. In particular, upon treatment with two different compounds, 2-deoxyglucose and FR054, inhibiting both HBP and protein N-glycosylation, these cells undergo apoptosis significantly more than PDAC cells expressing wild-type KRAS. Importantly, we also show that the combined treatment between FR054 and the pan-RAS inhibitor BI-2852 has an additive negative effect on cell proliferation and survival by means of the suppression of both Akt activity and cyclin D1 expression. Thus, co-inhibition of HBP and oncogenic RAS may represent a novel therapy for PDAC patients.